Human health effects of a changing global nitrogen cycle. Issue 5 (1st June 2003) - Townsend, Alan R.; Howarth, Robert W.; Bazzaz, Fakhri A.; Booth, Mary S.; Cleveland, Cory C.; Collinge, Sharon K.; Dobson, Andrew P.; Epstein, Paul R.; Holland, Elisabeth A.; Keeney, Dennis R.; Mallin, Michael A.; Rogers, Christine A.; et al.
Abstract : Changes to the global nitrogen cycle affect human health well beyond the associated benefits of increased food production. Many intensively fertilized crops become animal feed, helping to create disparities in world food distribution and leading to unbalanced diets, even in wealthy nations. Excessive air‐ and water‐borne nitrogen are linked to respiratory ailments, cardiac disease, and several cancers. Ecological feedbacks to excess nitrogen can inhibit crop growth, increase allergenic pollen production, and potentially affect the dynamics of several vector‐borne diseases, including West Nile virus, malaria, and cholera. These and other examples suggest that our increasing production and use of fixed nitrogen poses a growing public health risk.